1995
DOI: 10.1007/bf03010568
|View full text |Cite|
|
Sign up to set email alerts
|

Circulatory responses to laryngeal mask airway insertion or tracheal intubation in normotensive and hypertensive patients

Abstract: The effects of laryngeal mask airway (LMA) insertion and tracheal intubation on circulatory responses were studied in normotensive (n = 24) and hypertensive (n = 22) Les r$percussions de l'insertion du masque laryngd (ML) et de l~ntubation endotrachdale sur la circulation sont dtudides chez des normotendus (n = 24) et des hypertendus (n = 22). Au hasard et h double aveugle, le ML ou le tube endotrachdal est installd apr~s une induction au thiopentone avec relaxation musculaire ~ la succinylcholine. Compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 11 publications
10
50
3
Order By: Relevance
“…These findings are similar to those of previous studies . [6,7,8,9,11 ]. In Our study there was no difference in both the groups A and group N in terms of pulse rate, mean arterial blood pressure , SpO2, EtCO2 and peak airway pressures.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…These findings are similar to those of previous studies . [6,7,8,9,11 ]. In Our study there was no difference in both the groups A and group N in terms of pulse rate, mean arterial blood pressure , SpO2, EtCO2 and peak airway pressures.…”
Section: Discussioncontrasting
confidence: 48%
“…Studies by Cook, Shroff and co-workers(medianeffective time 15 s) corroborated with our study findings. [8,9] Sharma andcoworkers reported a mean insertion time of 13.51 s and 12 s, respectively for PLMA [6,10] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hemodynamic responses after laryngoscope-guided tracheal intubation are more pronounced in hypertensive patients. 4,5 S. Kihara et al found that both the ILMA and the LW provoke a milder stress response to tracheal intubation compared with the LS in hypertensive patients but not in normotensive patients. 6 Kohki Nishikawa et al concluded that the lightwand technique caused lesser hemodynamic changes in normotensive patients than the laryngoscope.…”
Section: Magnitude Of Pressor Responsementioning
confidence: 99%
“…Consequently, there is evidence that the magnitude of the pressor response varies with the intubation techniques. 16,17,18,19 In this study, we have divided nasotracheal intubation into three distinct stages namely -nasopharyngeal intubation, direct laryngoscopy, tracheal intubation and orotracheal intubation into two stages -direct laryngoscopy and tracheal intubation with the objective to identify the haemodynamic changes that occur during each stage of intubation through oral and nasal routes. We have used conventional laryngoscope and endotracheal tube wherever applicable.…”
Section: Introductionmentioning
confidence: 99%